Nummular headache: a case report of remission following ketogenic diet and botulinum toxin type A injections - Tereshko, Yan; Dal Bello, Simone; Lettieri, Christian; Belgrado, Enrico; Merlino, Giovanni; Gigli, Gian Luigi; Valente, Mariarosaria (Frontiers in Neurology, 2023)
Nummular headache is an unusual facial pain disorder with no evidence-based therapy recommendations. The ketogenic diet is an alternative therapy that demonstrated to be effective in migraineurs, but it was never used in the setting of nummular headache. We describe a 58-years old female patient with nummular headache successfully treated with a 6-months ketogenic diet and botulinum toxin type A injections. Ketogenic diet could be an effective alternative/complementary therapy in nummular headache patients although more studies are needed to confirm our results.